Swimming and training: Comparison between heuristic and prescriptive learning - Invernizzi, P. L.; Scurati, R.; Roione, G. C.; Michielon, G. (Biomechanics and Medicine in Swimming X, 2006)
Different opinions are given about the approaches of learning methods in swimming. Some supporting the prescriptive-cognitive theory, others the ecological-dynamic method, also called heuristic learning. Two groups of children attending a swimming school were taught by a prescriptive (subdivided) and by a heuristic methods. It seems that, in the swimming teaching, an ecological dynamic approach in the learning of the technique results to be more effective than a more rigid and defined prescribed method.